Molecular genetics of timing in intrinsic circadian rhythm sleep disorders. - Wijnen, H; Boothroyd, C; Young, M; Claridge-Chang, A (2002)
Recent advances in circadian biology are identifying key genes and the molecular clockworks they command. These biochemical systems provide new tools for evaluating clinically observed, intrinsic circadian rhythm sleep disorders. A striking example was last year's discovery of a point mutation in a human clock gene that produces a sleep phase syndrome. This finding suggested that other intrinsic sleep disorders may have genetic underpinnings, and that less debilitating variations in sleep/wake behavior may be revealed by molecular screening of known clock genes in broader human populations.